Simulation of multi-echelon supply chain inventory transshipment models at different levels. (July 2018) - Yan, Bo; Liu, Lifeng
An inventory transshipment model comprising manufacturers, distributors, and retailers based on multi-echelon supply chains is established using the system dynamics method. Thereafter, the single-, double-, three-, and four-chain inventory transshipment models at different levels are comparatively analyzed through simulation. Studies indicated that from the single- to four-chain inventory transshipment models, the average stock level minimally changed and declined. Meanwhile, the stability of the supply chain inventory improved continuously. The average customer requirement satisfaction rate of the inventory transshipment system consistently increases as the number of chains added to the transshipment system increases. However, the growth range of the average customer satisfaction rate continuously decreases with the increasing transshipment costs.